2014
DOI: 10.1016/j.nbd.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation in rats: Different targets induce similar antidepressant-like effects but influence different circuits

Abstract: Recent studies in patients with treatment-resistant depression have shown similar results with the use of deep brain stimulation (DBS) in the subcallosal cingulate gyrus (SCG), ventral capsule/ventral striatum (VC/VS) and nucleus accumbens (Acb). As these brain regions are interconnected, one hypothesis is that by stimulating these targets one would just be influencing different relays in the same circuitry. We investigate behavioral, immediate early gene expression, and functional connectivity changes in rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 78 publications
3
37
1
Order By: Relevance
“…Male Sprague Dawley rats (200 g) had stainless steel electrodes (cathodes; 250 μm in diameter) bilaterally implanted into the vmPFC or Acb, as previously described (Hamani et al, 2014;Rea et al, 2014). Similar electrodes connected to a bone screw implanted over the somatosensory cortex were used as anodes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Male Sprague Dawley rats (200 g) had stainless steel electrodes (cathodes; 250 μm in diameter) bilaterally implanted into the vmPFC or Acb, as previously described (Hamani et al, 2014;Rea et al, 2014). Similar electrodes connected to a bone screw implanted over the somatosensory cortex were used as anodes.…”
Section: Methodsmentioning
confidence: 99%
“…Controls had electrodes implanted in either the vmPFC or Acb but did not receive stimulation. DBS was conducted for 1 h at 100 μA or 300 μA, 130 Hz, and 90 μs (Hamani et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments from our lab have found that DBS applied to the rodent ventral medial prefrontal cortex (vmPFC) can also induce antidepressant-like effects (Hamani et al, 2010(Hamani et al, , 2012(Hamani et al, , 2014). This treatment model has provided a tool to directly probe how the nervous system is affected by stimulation and how physiological consequences are linked to depression.…”
Section: Introductionmentioning
confidence: 99%
“…This treatment model has provided a tool to directly probe how the nervous system is affected by stimulation and how physiological consequences are linked to depression. For example, recent work found that patterns of immediate early gene (IEG) expression across regions become less correlated between animals who have received vmPFC stimulation compared with correlations between non-stimulated animals (Hamani et al, 2014;Wheeler et al, 2013). This observation can be considered alongside demonstrations that brains of depressed patients exhibit abnormally high activity correlations ("functional connectivity") between the SCG and connected regions (Greicius et al, 2007;Berman et al, 2011;Zeng et al, 2012;Sambataro et al, 2013;Davey et al, 2012), raising the question of whether DBS may disrupt communication between brain networks that become pathologically hyperactive in depression.…”
Section: Introductionmentioning
confidence: 99%